Acute kidney injury successfully treated with autologous granulocyte colony‐stimulating factor‐mobilized peripheral blood CD34‐positive cell transplantation: A first‐in‐human report. (6th May 2021) - Suzuki, Hiroyuki; Ohtake, Takayasu; Tsukiyama, Toshitaka; Morota, Marie; Ishioka, Kunihiro; Moriya, Hidekazu; Mochida, Yasuhiro; Hidaka, Sumi; Sato, Tsutomu; Asahara, Takayuki; Kobayashi, Shuzo
Abstract: A 36‐year‐old man with severe acute kidney injury (AKI) was admitted to Shonan Kamakura General Hospital in Japan. He was diagnosed with refractory hypertension based on a severely elevated blood pressure of 224/116 mmHg and retinal, cardiac, and brain damage revealed by electrocardiogram, fundoscopy, and magnetic resonance imaging, respectively. Although hemodialysis was withdrawn following strict blood pressure control by an angiotensin receptor blocker, severe kidney insufficiency persisted. Therefore, we performed an autologous granulocyte colony‐stimulating factor‐mobilized peripheral blood CD34‐positive cell transplantation. Collected CD34‐positive cells were directly infused to both renal arteries. The patient's general condition was unremarkable after intervention, and the serum creatinine level gradually improved to 2.96 mg/dL 23 weeks after cell therapy. Although transient fever and thrombocytosis were observed after intervention, no major adverse events were observed. This patient is the first case in a phase I/II clinical trial of autologous granulocyte colony‐stimulating factor‐mobilized peripheral blood CD34‐positive cell transplantation for severe AKI with a CD34‐positive cell dose‐escalating protocol (trial number jRCTb030190231).